Bithiophene‐Cored, mono‐, bis‐, and tris‐(Trimethylammonium)‐Substituted, bis‐Triarylborane Chromophores: Effect of the Number and Position of Charges on Cell Imaging and DNA/RNA Sensing. Issue 56 (31st August 2021) - Berger, Sarina M.; Rühe, Jessica; Schwarzmann, Johannes; Phillipps, Alexandra; Richard, Ann‐Katrin; Ferger, Matthias; Krummenacher, Ivo; Tumir, Lidija‐Marija; Ban, Željka; Crnolatac, Ivo; Majhen, Dragomira; Barišić, Ivan; et al.
Abstract: The synthesis, photophysical, and electrochemical properties of selectively mono ‐, bis ‐ and tris ‐dimethylamino‐ and trimethylammonium‐substituted bis ‐triarylborane bithiophene chromophores are presented along with the water solubility and singlet oxygen sensitizing efficiency of the cationic compounds Cat 1+, Cat 2+, Cat(i) 2+, and Cat 3+ . Comparison with the mono ‐triarylboranes reveals the large influence of the bridging unit on the properties of the bis ‐triarylboranes, especially those of the cationic compounds. Based on these preliminary investigations, the interactions of Cat 1+, Cat 2+, Cat(i) 2+, and Cat 3+ with DNA, RNA, and DNApore were investigated in buffered solutions. The same compounds were investigated for their ability to enter and localize within organelles of human lung carcinoma (A549) and normal lung (WI38) cells showing that not only the number of charges but also their distribution over the chromophore influences interactions and staining properties. Abstract : Four selectively mono ‐, bis ‐ and tris ‐trimethylammonium‐substituted, bithiophene‐bridged bis ‐triarylboranes were synthesized and their potential biological applications were investigated including live cell imaging and photo‐induced cell death. It is demonstrated that their photophysical and electrochemical properties and their interactions with DNAs, RNA and cells, are strongly influenced by the number and distribution of charges within the compounds.